社會影響與系統特性對高齡者再次使用產銷履歷系統意願的影響─ 信任、態度與科技接受模型之整合 Effects of Social Influence and System Characteristics on Traceable Agriculture Product Reuse Intention of Elderly People: Integrating Trust and Attitude Using the Technology Acceptance Model - 林鴻洲 Hung-Chou Lin; 張德永 Te-Yung Chang; 郭素蕙 Su-Hui Kuo (National Taiwan Normal University, 2018)
本研究主要聚焦於當高齡者使用臺灣農產品安全追溯資訊網時，社會影響與系統特性對其知覺有用性與知覺易用性的影響；本研究更進一步探討消費者的知覺有用性與知覺易用性對消費態度與再次使用意願的影響。本研究針對高齡消費者發放紙本問卷，有效回收400份的問卷，並透過驗證式因素分析與結構方程式進行分析。研究結果顯示，樣本平均年齡為57.61歲，受測者有21.8%曾經使用過產銷履歷系統，有59%曾經購買過產銷履歷產品。研究結果發現高齡消費者的主觀規範、形象、能見度會影響其知覺有用性；而臺灣農產品安全追溯資訊網的資訊品質與系統品質會影響消費者的知覺易用性。另外，本研究也發現，對產銷履歷農產品制度的信任會正向影響消費者的再次使用意願。本研究提出實務建議，未來針對高齡者的科技創新及應用之接受度之培力訓練課程是必要的，因為高齡者可以藉此強化其友伴團體的社交網絡和學習行為，對其接受創新科技與新知分享會有增強作用；在高齡者健康教育與高齡消費者教育的相關議題中融入與產銷履歷的食農教育，在課程規劃、教學設計、教材研發，甚至資訊分享（如高齡消費者手冊）方面強化其深度與廣度；與高齡者的資訊溝通與社會學習議題之操作策略應該著重在體驗學習，藉由體驗學習，帶動高齡者在實作中的真實感 受，藉由理性認知、情感融入及技能之行為改變，更進一步達成其接受新知與提升生活知能的效果。 Products such as vegetables and fruits in markets in Taiwan have small green labels denoting that they are traceable agricultural products. This study investigated the effect of social influence and system characteristics on perceived usefulness (PU) and perceived ease of use (PEOU) regarding the Taiwan Agricultural and Food Traceability (TAFT) system. This study also examined the effects of PU and PEOU on attitudes and reuse intention, and employed confirmatory factor analysis and structural equation modelling to test the hypotheses. Questionnaires were developed and the measurement items were based on an extensive review of related studies to ensure content validity in addition to items from an original scale. Four hundred questionnaires from older adults were collected through a quantitative survey. The respondents were all aged between 50 and 90 years, with an average age of 57.61 years. Almost one quarter (21.8%) of respondents had experiences of using traceability quick response (QR) codes in 2016. Regarding purchase experience, 59% of the respondents had experiences of purchasing agricultural products using traceability QR codes. The results revealed that whereas subjective norms, image, and visibility have a positive effect on PU, information quality and system quality affected the PEOU of the TAFT system. Moreover, trust has a positive influence on reuse intention. A healthy diet plays a crucial role in the health promotion activities of elderly people. The findings could help those involved in the TAFT system improve their understanding of the attendant factors of PU and PEOU and promote positive attitudes in elderly people about this system, thereby increasing their reuse intentions.